2010
DOI: 10.1177/0962280210372453
|View full text |Cite
|
Sign up to set email alerts
|

A spatial beta-binomial model for clustered count data on dental caries

Abstract: One of the most important indicators of dental caries prevalence is the total count of decayed, missing or filled (DMF) surfaces in a tooth. These count data are often clustered in nature (several count responses clustered within a subject), over-dispersed, as well as spatially referenced (a diseased tooth might be positively influencing the decay process of a set of neighboring teeth). In this paper, we develop a multivariate spatial Beta-Binomial (BB) model for these data that accommodates both over-dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Examples of different scenarios, from different theoretical individuals, of random spells are given in Figure 2 . Dental caries can affect -or contribute to the disease affecting -a set of neighbouring teeth [Bandyopadhyay et al, 2011b], and a long-term effect of dental caries can be the initiation of new carious lesions. This means that, for each spell of caries initiation, new tooth decay can result from this spell until the age of observation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of different scenarios, from different theoretical individuals, of random spells are given in Figure 2 . Dental caries can affect -or contribute to the disease affecting -a set of neighbouring teeth [Bandyopadhyay et al, 2011b], and a long-term effect of dental caries can be the initiation of new carious lesions. This means that, for each spell of caries initiation, new tooth decay can result from this spell until the age of observation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a modification of risk factors at an individual level can lead to the development of new carious lesions, or inversely to the control of the carious disease (no new carious lesions for several years). It is also assumed that a particular tooth experiencing carious lesions tends to affect a set of neighbouring teeth in the same subject [Bandyopadhyay et al, 2011b]. Furthermore, it has been shown that caries development on one tooth could be related to caries development on other teeth, not necessarily in the direct neighbourhood of the initial lesion.…”
mentioning
confidence: 99%
“…For the spatial smoothing parameters ρk, a skewed prior is often used in spatial CAR modeling to encourage high spatial correlations, as seen in Diva et al (2007) and Bandyopadhyay et al (2011). Here, we assigned a Beta(1,1) prior based on our exploratory analysis, which is uniform between 0 and 1.…”
Section: Application: Whole-organ Histological and Genetic Map (Wohgm)mentioning
confidence: 99%
“…This is in stark contrast to traditional spatial referencing in disease mapping, where many responses are observed at each spatial location (Boehm et al , 2013). In addition, unlike other applications where the spatial neighbours are clearly defined by a grid, the spatial neighbourhood structure within the oral cavity is not clearly established (Bandyopadhyay et al , 2010).…”
Section: Introductionmentioning
confidence: 99%